2018
DOI: 10.1037/neu0000493
|View full text |Cite|
|
Sign up to set email alerts
|

The ipsilesional attention bias in right-hemisphere stroke patients as revealed by a realistic visual search task: Neuroanatomical correlates and functional relevance.

Abstract: Objective Right hemisphere stroke may cause an ipsilesional attention bias and left hemispatial neglect. Computerized time-limited tasks are more sensitive than conventional paper-pencil tests in detecting these spatial attention deficits. However, their frequency in the acute stage of stroke, the neuroanatomical basis and functional relevance for patients’ everyday life are unclear. Method A realistic visual search task is introduced, in which eye movements are recorded while the patient searches for paperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 63 publications
4
52
0
Order By: Relevance
“…We detected a rightward bias of exploratory fixations in the outer parts of the visual scene, most pronounced for the strongest type of modification (LHypo+RHyper) in the free viewing condition. Such a spatial asymmetry with avoidance of the far left and ''hyper-exploration'' of the far right is also found in patients with left hemispatial neglect (Behrmann et al, 1997;Sprenger et al, 2002;Müri et al, 2009;Delazer et al, 2018;Machner et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We detected a rightward bias of exploratory fixations in the outer parts of the visual scene, most pronounced for the strongest type of modification (LHypo+RHyper) in the free viewing condition. Such a spatial asymmetry with avoidance of the far left and ''hyper-exploration'' of the far right is also found in patients with left hemispatial neglect (Behrmann et al, 1997;Sprenger et al, 2002;Müri et al, 2009;Delazer et al, 2018;Machner et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Our modification could also not induce an enduring shift of exploratory eye movements towards the right hemifield as it is typically seen in patients with hemispatial neglect who exhibit an ipsilesional shift of the ''center of fixation'' of about 5-15 • (Karnath and Fetter, 1995;Machner et al, 2012Machner et al, , 2018. There are different possible explanations: first, our saliency modification might not have been strong enough to elicit such a pronounced shift of the center of fixation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the observation of errorless performance for the most lateralized ipsilesional locations might depend on ceiling effects. Recently Machner et al (2018) showed that the most severe neglect patients they tested were slower than controls in detecting ipsilesional targets in a Posner detection task, while in a search task they processed the most ipsilesional targets with the same accuracy as healthy controls (i.e., almost errorless).…”
Section: Introductionmentioning
confidence: 98%
“…This task has been proven very sensitive in detecting even mild subclinical signs of lateralized inattention, otherwise missed by established paper-and-pencil tests and clinical observation. 34 Eye movements were recorded in order to obtain information on an ipsilesional oculomotor/attention bias during overt shifts of spatial attention (as opposed to the rather reflexive pattern of an optokinetic nystagmus in the OKS task). Based on the horizontal fixation distribution of eye movements on the screen, we calculated the center of fixation ( CoF ), which corresponds to the median x-position on the screen from where 50% of all fixations were located on the left and 50% on the right.…”
Section: Methodsmentioning
confidence: 99%